515. EXOCRINE PANCREATIC FUNCTION IN PATIENTS AFTER ESOPHAGECTOMY; IS TREATMENT WITH PANCREATIC ENZYMES NECESSARY?. (24th September 2022) - Blonk, Lotte; Wierdsma, NJ; Kazemier, G; Gisbertz, SS; van Berge Henegouwen, MI; van der Peet, DL; Straatman, J
Abstract: Symptoms of malabsorption, such as diarrhea, steatorrhea, or unintended weight loss, are often reported by patients after esophagectomy for cancer. The etiology of these symptoms is hypothesized to be multifactorial, with exocrine pancreatic insufficiency being described as one of the possible contributing causes. Symptoms of malabsorption are therefore often treated with pancreatic enzymes. This study aimed to measure the exocrine pancreatic function to determine whether there is an indication for pancreatic enzymes after esophagectomy. This prospective study included patients after esophagectomy for cancer in a stable postoperative situation (≥6 months after surgery) without signs of recurrent disease. Patients with and without pancreatic enzymes or symptoms of malabsorption were included. Exocrine pancreatic function was measured by fecal elastase-1 (FE-1) and fecal fat excretion. Three-day stool collections were performed to measure mean daily fecal fat excretion (g/d). Combined with a four-day (weighted) nutritional diary, to determine the mean daily fat intake (g/d), the percentage of fat absorption was calculated. Patients who were already treated with pancreatic enzymes stopped at least two days before stool collection. This study included 38 patients after esophagectomy for cancer. Exocrine pancreatic function was measured after a median postoperative follow-up of 20 months (range 6-45). Low FE-1 (<200 μg/g) levels were found in seven patients (18%). Of these patients, one patient also had fat malabsorption (fat absorption <85%). Prior to participation in this study, 11 patients (28%) already received treated with pancreatic enzymes because of symptoms of malabsorption. In one of these patients (9%) low FE-1 levels were found and in three patients (27%) fat malabsorption was diagnosed. These preliminary results indicate that, based on FE-1 levels, the secretion of pancreatic enzymes after esophagectomy is only impaired in a subgroup of patients. Most often this did not lead to malabsorption of fat. Based on these results routine prescription of pancreatic enzymes is not recommended in patients after esophagectomy, however a trial prescription can be considered in patients suffering from gastrointestinal complaints of malabsorption.